2020
DOI: 10.1007/s11306-020-1646-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification to species level of live single microalgal cells from plankton samples with matrix-free laser/desorption ionization mass spectrometry

Abstract: Introduction Marine planktonic communities are complex microbial consortia often dominated by microscopic algae. The taxonomic identification of individual phytoplankton cells usually relies on their morphology and demands expert knowledge. Recently, a live single-cell mass spectrometry (LSC-MS) pipeline was developed to generate metabolic profiles of microalgae. Objective Taxonomic identification of diverse microalgal single cells from collection strains and plankton samples based on the metabolic fingerprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…While some of these metabolites have reported observations in seawater, we have yet to resolve their distributions, functions, and cycling in natural microbial populations. New analytical approaches including single-cell imaging metabolomics allow resolution of metabolites exchanged in microbial consortia (Baumeister et al, 2020;Vallet et al, 2021). Analytical methods have also recently become available to measure polar metabolites like sulfonates, amino acids, and sugars in the dissolved fraction of seawater (Widner et al, 2021), opening up new avenues to compare concentrations of intracellular and excreted metabolites relevant to nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of these metabolites have reported observations in seawater, we have yet to resolve their distributions, functions, and cycling in natural microbial populations. New analytical approaches including single-cell imaging metabolomics allow resolution of metabolites exchanged in microbial consortia (Baumeister et al, 2020;Vallet et al, 2021). Analytical methods have also recently become available to measure polar metabolites like sulfonates, amino acids, and sugars in the dissolved fraction of seawater (Widner et al, 2021), opening up new avenues to compare concentrations of intracellular and excreted metabolites relevant to nutrient cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Isotope-based tools like Chip-SIP have provided highthroughput means to quantify taxon-specific incorporation of stable isotope-labeled substrates (Mayali et al, 2012). Highresolution metabolomics studies of cultures and field samples have demonstrated the value of metabolic fingerprints in distinguishing plankton (Baumeister et al, 2020) and identified underexplored sulfur-containing metabolites gonyol, dimethylsulfonioacetate (DMSAc), dimethylsulfoxonium propionate (DMSOP) (Gebser and Pohnert, 2013;Thume et al, 2018;Gebser et al, 2020) and nitrogen-containing metabolites trigonelline and homarine (Heal et al, 2021) implicated in metabolic exchange among microbial taxa.…”
Section: Introductionmentioning
confidence: 99%
“…This identification method was initially used for the identification of species of bacteria, fungi, and viruses (e.g., Claydon et al, 1996;Fenselau and Demirev, 2001), and is still widely used (e.g., Seng et al, 2010;Chalupová et al, 2014;Singhal et al, 2015). In addition, MALDI-TOF MS has been used for species identification of microalgae (Baumeister et al, 2020), microorganisms (Maier et al, 2006) and various metazoan taxa including insects (Feltens et al, 2010), fish (Volta et al, 2012;Shao and Bi, 2020), and calanoid copepods (Riccardi et al, 2012;Laakmann et al, 2013;Bode et al, 2017). Previous studies with several taxa as study subjects confirmed that MALDI-TOF MS is a reliable and fast alternative method for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gaining an understanding of the physiological status of phytoplankton cells holds excellent promises for environmental research. Besides, chemotyping of microalgae via pipelines that utilize live single-cell MS is currently exploited for taxonomic identification [99]. Despite the broad applications in environmental research, initial studies on algal metabolomics mostly focused on the model organism Chlamydomonas reinhardtii because of applications in the biotechnology industry and biofuel production [100].…”
Section: Spatially Resolved Metabolomics In Plants: Current Status Cmentioning
confidence: 99%